2022
DOI: 10.3389/fcimb.2022.998313
|View full text |Cite
|
Sign up to set email alerts
|

The impact of periodontitis on vascular endothelial dysfunction

Abstract: Periodontitis, an oral inflammatory disease, originates from periodontal microbiota dysbiosis which is associated with the dysregulation of host immunoinflammatory response. This chronic infection is not only harmful to oral health but is also a risk factor for the onset and progress of various vascular diseases, such as hypertension, atherosclerosis, and coronary arterial disease. Vascular endothelial dysfunction is the initial key pathological feature of vascular diseases. Clarifying the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 138 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…Periodontitis is a proposed risk factor for hypertension (Del Pinto et al, 2020). The inflammatory mediators produced in periodontitis (e.g., IL‐6 and TNF‐α) affect systemic endothelial function and may lead to hypertension (Li et al, 2022). Additionally, bacteraemia caused by oral microflora may directly affect vascular dysfunction (Muñoz Aguilera et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is a proposed risk factor for hypertension (Del Pinto et al, 2020). The inflammatory mediators produced in periodontitis (e.g., IL‐6 and TNF‐α) affect systemic endothelial function and may lead to hypertension (Li et al, 2022). Additionally, bacteraemia caused by oral microflora may directly affect vascular dysfunction (Muñoz Aguilera et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“… 77 Previous research has shown that patients with periodontitis had lower levels of functional capillary density, capillary widths, resting red blood cell velocity, post-ischemic peak flow, and endothelium-independent vasodilatation. 75 It has been shown that the presence of P. gingivalis in periodontal infections affects matrix metalloproteinase-2/tissue inhibitor of metalloproteinases 2 complex, inflammatory mediators production, chemokines like CX3C chemokine ligand 1, IL-8 and monocyte chemotactic protein-1, and myeloperoxidase within vascular endothelial cells. 75 Because of this, leukocytes and monocytes are better able to migrate to and adhere to the endothelium of blood arteries.…”
Section: Periodontic Events and Cardiovascular Riskmentioning
confidence: 99%
“… 75 It has been shown that the presence of P. gingivalis in periodontal infections affects matrix metalloproteinase-2/tissue inhibitor of metalloproteinases 2 complex, inflammatory mediators production, chemokines like CX3C chemokine ligand 1, IL-8 and monocyte chemotactic protein-1, and myeloperoxidase within vascular endothelial cells. 75 Because of this, leukocytes and monocytes are better able to migrate to and adhere to the endothelium of blood arteries. These immune cells have also been demonstrated to release extra inflammatory factors while transporting periodontal bacteria into the arterial wall.…”
Section: Periodontic Events and Cardiovascular Riskmentioning
confidence: 99%
“…[7] More than 40% of individuals in the United States have periodontitis, a prevalent inflammatory oral disease that is the primary cause of tooth loss and is thought to influence the lives of individuals, their ability to chew, and nutritional status. [8][9][10][11][12][13] Innate and adaptive immunity are both implicated in the pathophysiology of this chronic inflammatory illness of the oral cavity, which is characterized by the creation of periodontal pockets, loss of attachments, and resorption of alveolar bone. [14] Periodontitis has grown to be a significant public health issue and a growing strain on healthcare systems as the world's population ages.…”
Section: Introductionmentioning
confidence: 99%